The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0268340
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter international assessment of a SARS-CoV-2 RT-LAMP test for point of care clinical application

Abstract: Continued waves, new variants, and limited vaccine deployment mean that SARS-CoV-2 tests remain vital to constrain the coronavirus disease 2019 (COVID-19) pandemic. Affordable, point-of-care (PoC) tests allow rapid screening in non-medical settings. Reverse-transcription loop-mediated isothermal amplification (RT-LAMP) is an appealing approach. A crucial step is to optimize testing in low/medium resource settings. Here, we optimized RT-LAMP for SARS-CoV-2 and human β-actin, and tested clinical samples in multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“… 376 , 378 Since the emergence of SARS-CoV-2, many RT-LAMP assays have been developed for the diagnosis of this virus in several types of clinical samples, including saliva, serum, nasopharyngeal swabs, oropharyngeal swabs, and urine. 370 , 379 386 In general, RT-LAMP assays have been designed for different targets in the SARS-COV-2 genome (ORF1ab, N protein, E protein, RdRP, and M protein), and the clinical performances of many RT-LAMP assays have been compared with that of RT-qPCR. 315 , 385 , 387 Efforts to decrease the cost and simplify the RT-LAMP workflow for testing patient samples are in progress using protocols without RNA extraction from patient specimens and in-house-produced enzymes, 388 390 with the possibility to scale up COVID-19 diagnostics.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“… 376 , 378 Since the emergence of SARS-CoV-2, many RT-LAMP assays have been developed for the diagnosis of this virus in several types of clinical samples, including saliva, serum, nasopharyngeal swabs, oropharyngeal swabs, and urine. 370 , 379 386 In general, RT-LAMP assays have been designed for different targets in the SARS-COV-2 genome (ORF1ab, N protein, E protein, RdRP, and M protein), and the clinical performances of many RT-LAMP assays have been compared with that of RT-qPCR. 315 , 385 , 387 Efforts to decrease the cost and simplify the RT-LAMP workflow for testing patient samples are in progress using protocols without RNA extraction from patient specimens and in-house-produced enzymes, 388 390 with the possibility to scale up COVID-19 diagnostics.…”
Section: Diagnosismentioning
confidence: 99%
“…Considering its advantages of high specificity and sensitivity, rapid amplification, simple operation, and low cost, RT-LAMP has potential applications for the diagnosis of many infectious diseases. , Since the emergence of SARS-CoV-2, many RT-LAMP assays have been developed for the diagnosis of this virus in several types of clinical samples, including saliva, serum, nasopharyngeal swabs, oropharyngeal swabs, and urine. , In general, RT-LAMP assays have been designed for different targets in the SARS-COV-2 genome (ORF1ab, N protein, E protein, RdRP, and M protein), and the clinical performances of many RT-LAMP assays have been compared with that of RT-qPCR. ,, Efforts to decrease the cost and simplify the RT-LAMP workflow for testing patient samples are in progress using protocols without RNA extraction from patient specimens and in-house-produced enzymes, with the possibility to scale up COVID-19 diagnostics. With regard to the limit of detection (LoD), the majority of RT-LAMP assays should have LoDs ranging from 200 to 100 copies per reaction, , while a few have demonstrated LoDs as low as 10 copies per reaction or even 1 copy per reaction. Currently, there are 14 diagnostic devices based on RT-LAMP assays that have been granted Emergency Use Authorization (EUA) by the FDA ().…”
Section: Diagnosismentioning
confidence: 99%
“…Numerous studies on RNA clinical samples with a high Cq value (>30), in which the results did not pick up by the RT-LAMP assay or took a longer time > 35 min to be detected, which could affect some negative samples and might cause false-positive results [ 32 , 33 , 34 ]. Other studies found the cutoff of RT-LAMP when the Cq value was 32 or more [ 35 , 36 ]. Therefore, further optimization is needed to identify the Cq breakpoint for this assay and to improve it by increasing the input amount of RNA in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement was evident with final concentrations between 40 and 60 mM in a 25 µL reaction volume, with 40 mM being the optimum recommended concentration https://international.neb.com 24 . Most studies reported this enhancement from GuHCl on RNA-extracted clinical samples but not in direct ones 22 , 23 . Based on that, we used 40 mM GuHCl in the colorimetric and fluorometric RT-LAMP reactions; both resulting in 3–7-min earlier amplifications in positive reactions with GuHCl.…”
Section: Discussionmentioning
confidence: 95%